Comparison of the morphology of the adult males of the rhizoecine, phenacoccine and pseudococcine mealybugs (Hemiptera: Sternorrhyncha: Coccoidea), with the recognition of the family Rhizoecidae Williams - Hodgson, Chris (Zootaxa, 2012)
In the past, the morphology of adult males of Coccoidea has provided strong support for diagnosing the higher taxonstatus of scale insects (Coccoidea). In particular, studies on adult male morphology have produced some of the stron-gest evidence for considering the Putoidae and Eriococcidae (as then defined) as separate families from the Pseudo-coccidae. This paper uses adult male morphology to assess the relationships of the Pseudococcidae and the hypogaeicand myrmecophilous mealybugs. The latter most often are classified as a subfamily (Rhizoecinae) of the Pseudococ-cidae. In order to diagnose the latter taxa, the adult males of fifteen named species of hypogaeic rhizoecine mealybugs(Kissrhizoecus hungaricus Kozár & Konczné Benedicty, Rhizoecus cacticans (Hambleton), Rh. coffeae Laing, Rh.dianthi Green, Rh. falcifer Künckel d’Herculais, Rh. kazachstanus Matesova, Ripersiella cryphia (Williams), Ri.hibisci (Kawai & Takagi), Ri. kondonis (Kuwana), Ri. malschae (Williams), Ri. puhiensis (Hambleton), Capitisetellamigrans (Green) and Pseudorhizoecus proximus Green) plus two unidentified Ripersiella species are described. Inaddition, the adult males of a Xenococcus sp., three Eumyrmococcus spp. and two Neochavesia spp. are illustratedfrom previously published papers and the adult male of another Neochavesia sp. is described and illustrated. In orderto compare the diagnoses of the above taxa with that of adult males of Pseudococcidae (minus the Rhizoecinae), theadult males of two apterous pseudococcid mealybugs are described or redescribed: Asaphococcus agninus Cox andthe myrmecophilous Promyrmococcus dilli Williams, both belonging to the Pseudococcinae. In addition, threemacropterous Pseudococcidae, namely Phenacoccus solenopsis Tinsley (Phenacoccinae), Planococcus glaucus(Maskell) and Maconellicoccus hirsutus (Green) (Pseudococcinae) are also described and/or illustrated. Prior to thisstudy, the hypogaeic and myrmecophilous mealybugs generally were included in the subfamily Rhizoecinae of thePseudococcidae, with the hypogaeic mealybugs in tribe Rhizoecini and the myrmecophilous mealybugs in Xenococ-cini. Based on the present study and on phylogenetic data, it is concluded that the rhizoecine mealybugs form a sepa-rate family from the Pseudococcidae — Rhizoecidae Williams. This family is considered here to include twosubfamilies, Rhizoecinae Williams and Xenococcinae Tang. Based on adult male characters, there is little support forthe present generic divisions of the Rhizoecinae. Keys are given for separating the adult males of Rhizoecidae from those of Pseudococcidae, and for separating the known adult males within each subfamily.